Pengaruh Hasil UAV atau Drone Dalam Inventarisasi Lahan Untuk Niatan Penggunaan Pada Kegiatan Pembebasan Lahan - Ezra Farabi Umar (Lambung Mangkurat University Press, 2022)
UAV or Drone shows a very good influence in land inventory activities for land acquisition activities based on their ability to collect data. Currently, at least UAVs or drones can provide five types of data in the form of orthophoto maps, topographic maps, high-resolution photos, videography and 3D images. This study aims to find out how the views of land acquisition actors in the adoption of drone technology and their views on the data that can be collected by UAVs or drones. This research was conducted using the Framework Technology Acceptance Model covering 280 respondents who contained land acquisition actors from various sectors of work ranging from plantations, mining, petroleum, and civil works. The method in this study is a quantitative method with a research instrument in the form of a questionnaire. The data that has been collected is then analyzed using SEM PLS (Partial Least Square Structural Equation Modeling) analysis using the help of the SmartPLS program. The results of the study show that the perceived ease of use, perceived usefulness, and output of drones affect the intention of land acquisition actors to adopt UAV or Drone technology